ISCORD 2013 : planning for sustainable cold regions : proceedings of the 10th International Symposium on Cold Regions Development, June 2-5, 2013, Anchorage, Alaska - Zufelt, Jon E. (American Society of Civil Engineers, 2013)
Proceedings of the 10th International Symposium on Cold Regions Development, held in Anchorage, Alaska, June 2-5, 2013. Sponsored by the Technical Council on Cold Regions Engineering and the Alaska Section of the American Society of Civil Engineers in cooperation with the International Association for Cold Regions Development Studies (IACORDS). This collection contains 79 peer-reviewed papers that bring together the current state of knowledge on a variety of topics and techniques in research, planning, design, engineering, construction, and operations in the cold regions of the world. This proceedings will be of interest to engineers, scientists, and government officials. --